Food Peptides for the Nutricosmetic Industry - Irene Dini; Andrea Mancusi (MDPI AG, 2023)
In recent years, numerous reports have described bioactive peptides (biopeptides)/hydrolysates produced from various food sources. Biopeptides are considered interesting for industrial application since they show numerous functional properties (e.g., anti-aging, antioxidant, anti-inflammatory, and antimicrobial properties) and technological properties (e.g., solubility, emulsifying, and foaming). Moreover, they have fewer side effects than synthetic drugs. Nevertheless, some challenges must be overcome before their administration via the oral route. The gastric, pancreatic, and small intestinal enzymes and acidic stomach conditions can affect their bioavailability and the levels that can reach the site of action. Some delivery systems have been studied to avoid these problems (e.g., microemulsions, liposomes, solid lipid particles). This paper summarizes the results of studies conducted on biopeptides isolated from plants, marine organisms, animals, and biowaste by-products, discusses their potential application in the nutricosmetic industry, and considers potential delivery systems that could maintain their bioactivity. Our results show that food peptides are environmentally sustainable products that can be used as antioxidant, antimicrobial, anti-aging, and anti-inflammatory agents in nutricosmetic formulations. Biopeptide production from biowaste requires expertise in analytical procedures and good manufacturing practice. It is hoped that new analytical procedures can be developed to simplify large-scale production and that the authorities adopt and regulate use of appropriate testing standards to guarantee the population's safety.